2015
DOI: 10.1074/jbc.a110.181164
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar epithelial cells undergo epithelial-to-mesenchymal transition in response to endoplasmic reticulum stress.

Abstract: PAGE 30974:The same Western blot images were mistakenly used to represent phosphorylated eIF2␣ (peIF2␣) in both RLE6TN cells that had not been transfected (Fig. 1B) and in cells that had been transfected with empty vector or with vectors expressing wild type or mutant surfactant protein C (Fig. 1C). The correct Western blot image for phosphorylated eIF2␣ in transfected cells that we have obtained from a new experiment is shown in the revised Fig. 1C. This change does not affect the interpretation of the result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
76
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(84 citation statements)
references
References 0 publications
5
76
0
3
Order By: Relevance
“…36 Recent studies of endoplasmic reticulum stress-induced EMT in alveolar epithelial cells and ischemia-reperfusion-induced ALI of rat have shown that apoptotic cell death, in a Src kinase-dependent manner, may represent an escape mechanism for the stressed cells to reduce production of inflammatory proteins and rely on the duration and extent of epithelial cell injury. [19][20][21] We demonstrated that high-V T mechanical ventilation-induced apoptosis of murine airway epithelial cells with characteristic findings of highly condensed and fragmented heterochromatin. Apoptotic cell death, lung injury, severe hypoxemia and computer tomographic findings of fibrogenesis, such as reticular abnormality and honeycombing were attenuated in Src-deficient mice and pharmacologic inhibition with PP2, suggesting the involvement of the Src pathway in regulating EMT and epithelial apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…36 Recent studies of endoplasmic reticulum stress-induced EMT in alveolar epithelial cells and ischemia-reperfusion-induced ALI of rat have shown that apoptotic cell death, in a Src kinase-dependent manner, may represent an escape mechanism for the stressed cells to reduce production of inflammatory proteins and rely on the duration and extent of epithelial cell injury. [19][20][21] We demonstrated that high-V T mechanical ventilation-induced apoptosis of murine airway epithelial cells with characteristic findings of highly condensed and fragmented heterochromatin. Apoptotic cell death, lung injury, severe hypoxemia and computer tomographic findings of fibrogenesis, such as reticular abnormality and honeycombing were attenuated in Src-deficient mice and pharmacologic inhibition with PP2, suggesting the involvement of the Src pathway in regulating EMT and epithelial apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…14,19,20 Src inhibitors that are used in vivo may suppress inflammatory responses, involving neutrophils, monocytes, macrophages, endothelial and epithelial cells. 21,22 Given the absence of a proven effective treatment for acute lung injury (ALI) and EMT, Src inhibition may provide an attractive target in the devastating process of patients with ARDS. 14,23 In this high-V T ventilation-induced lung injury model of mice pretreated with bleomycin, we compared the effects among various V T of mechanical ventilation, the correlation of EMT to fibroblast accumulation and epithelial apoptosis, and the production of PAI-1 and TGF-b1 using pharmacological inhibitors PP2 and Src-deficient mice.…”
mentioning
confidence: 99%
“…48,49 In our study, a protective effect of TUDCA on TGF-β1-induced EMT was associated with an amelioration of Smad2/3 activation, suggesting that the Smad2/3 pathway is a key mediator of EMT. Tanjore et al 20 also demonstrated an activation of Smad2/3 in TM-treated alveolar epithelial cells and reported that either a Smad2/3 inhibitor or siRNA targeting Smad2/3 attenuated EMT of pulmonary alveolar cells.…”
Section: Discussionmentioning
confidence: 99%
“…18 ER stress also induced EMT in cultured alveolar epithelial cells by activating MAPKinase, Smad and Src. 20 The role of the UPR and ER stress has been demonstrated in idiopathic pulmonary fibrosis, as well as glomerulonephritis, diabetic nephropathy and drug-induced renal damage. 17,19,43,44 Despite ample evidence regarding the role of ER stress in organ fibrosis, the about ER stress and peritoneal fibrosis remain very limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation